Teologi Iman Berbasis Amsal 3 : 1–8 Upaya Penguatan Rohani di GKPI Jemaat Khusus Pandumaan Dolok Sanggul - Benny Christian Hutabarat; Iwan Setiawan Tarigan (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study raises the theme of Theology of Faith Based on Proverbs 3:1–8 in an effort to strengthen the spiritual life of the members of the Indonesian Protestant Christian Church (GKPI) Pandumaan Special Congregation amidst the challenges of the modern era. Proverbs 3:1–8 teaches important theological principles about living a strong faith, living in wisdom, faithfulness, and fearing God. Through qualitative and quantitative approaches, this study found that many church members experience wavering faith due to the influence of secular culture, technological advances, and social pressures. This study interprets Proverbs 3:1–8 as a call to trust God with all our hearts, not to lean on our own understanding, and to live in real loyalty and goodness. Wisdom in this context is understood not only as rational intelligence, but also as the result of total submission to God's will. This study emphasizes that strong faith is the foundation for a healthy and strong spiritual life amidst today's pluralism and spiritual crisis. Thus, faith rooted in the word and wisdom of God becomes a theological solution for church members to remain firm as the light and salt of the world.